Earthquake Damages and Disaster Prevention of Aboveground Storage Tanks - Shoichi Yoshida (EPI International Journal of Engineering, 2018)
Severe damages in aboveground storage tanks (AST) have been often experienced due to earthquakes in Japan. In this paper, earthquake damages of ASTs which occurred for the last several decades are reviewed. These are damages in the 1964 Niigata Earthquake, the 1978 Miyagi Earthquake, the 1983 Sea of Japan Earthquake, the 1995 Kobe Earthquake, the 2003 Hokkaido Earthquake and the 2011 Great East Japan Earthquake. The damages of ASTs can be classified into 3 types in accordance with the characteristics of earthquake. These are the impulsive motion due to a high frequency earthquake, the sloshing motion due to a low frequency earthquake and the tsunami attack. In the impulsive motion, buckling of sidewall plates and uplift of sidewall-to-bottom joints occurred. In the sloshing motion, sinking of floating roofs into liquid and buckling of sidewall-to-roof joints occurred. In the tsunami attack, ASTs moved and overturned to leak oil.